The influence of iron supplementation in pregnant women to the occurrence of low birth weight (LBW) babies in Palu, Central Sulawesi - R. Detty Siti Nurdiati Z, Sri Restu Djaswadi Dasuki (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Low birth weight (LBW) babies remains a major problem world wide as it causes a high rate ofneonatal morbidity and mortality. One effort to reduce the prevalence of LBW babies is byproviding iron supplementation to the pregnant women. The aim of this study was to examinethe relationship between iron supplementation program and prevalence of LBW babies in Palu,Central Sulawesi. This was an observational study with case control design. Subjects were allLBW babies from mothers that had accepted iron supplementation during pregnancy. Samplesize in this study was 87 for case and 87 for control. Bivariate analysis showed that ironsupplementation that not comply the program had a significant correlation with prevalence ofLBW babies (p=0.01). Other significant factors include abnormal hemoglobin level (p=0.01),body mass index (BMI) (p=0.02), educational level (p=0.02), multiparity (p=0.03), andgestational age (prematurity) (p=0.03). Multivariate analysis revealed that the strongest riskfactor for the occurrence of LBW babies was iron supplementation that not comply the program(OR= 3.82; 95% CI: 1.77- 8.22). Other risk factors were hemoglobin level (OR= 3.45; 95% CI:1.59-7.49), BMI (OR= 2.27; 95% CI: 1.05-4.91), gestational age (OR= 3.11; 95% CI: 1.45-6.67), multiparity (OR= 2.98, 95% CI: 1.36-6.51), and educational level (OR= 2.38, 95% CI:1.12-5.03). Based on the analysis, the strongest risk factors that affected the prevalence of LBWwas iron supplementation, abnormal hemoglobin level, gestational age, multiparity and educationlevel. In conclusion, iron supplementation during pregnancy that not comply with the programwas the strongest risk factor of LBW babies. The prevalence of LBW babies can be reduced bycontrolling of iron supplementation, hemoglobin level, BMI, gestational age, parity and education.